Grenzüberschreitende Daseinsvorsorge in der Euregio Maas-Rhein. Was kann die Euroregion Pro Europa Viadrina lernen? - Unfried, Martin (Grenzüberschreitende Daseinsvorsorge. Stand und Perspektiven in europäischen Verflechtungsräumen, 2025)
Abstract: „Die euregionalen Partner in der Euregio Maas-Rhein, am Dreiländereck Deutschland/Niederlande/Belgien, haben in den letzten Jahrzehnten viel Erfahrung gesammelt beim Aufbau von Netzwerken im Bereich der öffentlichen Dienstleistungen. Der Artikel stellt wesentliche Netzwerke vor, wobei ausführlicher eingegangen wird auf die Entwicklungen im Bereich der Notfallrettung und der Gesundheitsversorgung, des öffentlichen Nahverkehrs und der Wohnungsmarktpolitik.“
Keywords: Euregio Maas-Rhein; Medizinische Versorgung; Rettungswesen; Wohnungsmarkt; Wohnungspolitik; Öffentlicher Personennahverkehr

Outlaw motorcycle gangs in the Meuse Rhine Euregion. Exploration of the phenomenon, omcg-related crime and the public response to omcgs - Geurtjens, Kim C. P. (Eleven, 2022)
Abstract: „Outlaw motorcycle gangs (OMCGs) have been increasingly viewed as a threat to society. Members have been associated with disturbances of public order as well as various forms of organized crime. In response, the authorities in the Netherlands, Germany, and Belgium have each implemented their own zero-tolerance strategies to prevent and repress outlaw biker crime and deviance. In the cross-border Meuse Rhine Euregion, where the three countries intersect, the national borders may provide opportunities to outlaw bikers while at the same time limiting authorities in their response. In examining the role of the border, this book deals with the history of OMCGs and the responses in each country, the authorities involved in the response, and contemporary problems in the Meuse Rhine Euregion. This book is intended for policy makers and practitioners working in the field of organized crime and public disorder committed by outlaw bikers, especially those working in cross-border regions.“
Inhaltsverzeichnis: https://swbplus.bsz-bw.de/cgi-bin/result_katan.pl?item=bsz1809288029inh.htm
Keywords: Euregio Maas-Rhein; Grenzüberschreitende Kooperation; Organisierte Kriminalität

Zo dicht bij elkaar, maar toch heel anders. Eigendomsverhoudingen, productie en werkgelegenheid in de vier mijnbouwgebieden in het Maas-Rijngebied - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2016)
Keywords: Arbeitsmarkt; Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Werk in de marge? Grensarbeid vanuit het Nederlandse naar het Duitse deel van de Euregio Maas-Rijn, 1960–2000 - Bouwens, Sophie (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2005)
Keywords: Euregio Maas-Rhein; Grenzarbeitnehmer; Südlimburg (Niederlande)

The Maas-Rhine Euroregion. A Laboratory for European Integration? - Knippenberg, Hans (Geopolitics, 2004)
„The transborder and trilingual Maas–Rhine Euroregion is often presented as a laboratory for European integration. The authorities in the region promote the image of a region that has ‘always’ been a unity, but which is divided by artificial boundaries – ‘scars of history’ – as a result of power politics. In this essay this image is confronted with the reality of the cross-border interactions and identities of the people involved. This confrontation leads to the conclusion that although there is political, economic and cultural cooperation in the region, the region is not at all politically, economically and culturally integrated. The national border as a physical barrier may have been removed, but the economic, social, juridical and cultural barriers are still there. The unification and integration of the citizens living in the region is being impeded by conflicting national systems of law and regulations, by communication and information media focused on national issues, by nationally oriented infrastructure, and especially by strongly different national cultures and identities. The consequences for European integration in general are analysed by comparing this regional integration with the national integration and nation-building policies of the past.“
Keywords: Euregio Maas-Rhein; Europäische Integration; Grenzüberschreitende Kooperation

Historische interacties in de Euregio Maas-Rijn. Migratiestromen in een grensgebied - Korres, Achim (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer

Paradoxen van de grens. Ongelijke ontwikkeling, grensoverschrijdende mobiliteit en de vergelijkende geschiedenis van de Euregio Maas-Rijn - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg - Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2001)
Keywords: Euregio Maas-Rhein; Grenzverkehr

Samenwerking? Er zijn grenzen! Onderzoek naar de invloed van de culturele factor op het proces van economische en politiek-bestuurlijke integratie in de Euregio Maas-Rijn - Beek, Cobi van (Barjester, Meeuwes, 1996)
Keywords: Euregio Maas-Rhein; Grenzüberschreitende Kooperation; Hochschulschrift; Soziokultureller Faktor